العلاقة التربوية بين سلوك المعلم واتجاهات تلاميذه في المرحلة الابتدئية - حريري، سها عبد الله
This study to shed light on the subject of the educational relationship between the teacher and the students in the class، and to prove the existence of gap in this relationship، and to explain the reasons that led to exist this gap between the teacher and the students. As well as the consequences of the existence of a large amount of misconduct and negative behaviour that affects students، and then propose a range of solutions that can contribute to improve the educational relationship between teachers and students. The researcher followed a set of methodologies that dealt with the study’s subject، through the analytical approach, the descriptive analytical approach, and interviews; then the researcher criticized the teacher's behavior which is the focus of this study. The study concluded several results، the most important of which is: proof that there is a gap between teacher and students in terms of interaction. The study ended with a set of recommendations.